Factors Associated With Family Latrine Ownership and Diarrheal Incidence Among Under-Five Children at Rangas Primary Health Center, Mamuju Regency - Anwar Anwar; Amran Amran; Ulmi Mahmud (Jurnal Ners, 2026)
Diarrheal disease remains a major public health problem among under-five children and is closely associated with environmental sanitation and household health behaviors. This study aimed to analyze factors influencing family latrine ownership and diarrheal incidence among under-five children in the working area of Rangas Primary Health Center, Mamuju Regency. An observational analytic study with a cross-sectional design was conducted involving 189 under-five children selected using proportional random sampling. Data were analyzed using path analysis to examine direct and indirect effects of behavioral and environmental factors on diarrheal incidence, with family latrine ownership as an intervening variable. The results indicated that knowledge, attitude, hygiene practices, and availability of clean water had significant effects on family latrine ownership, with clean water availability being the most dominant factor. Diarrheal incidence among under-five children was significantly influenced by knowledge, hygiene practices, health workers’ roles, and latrine ownership, with hygiene practices emerging as the strongest determinant. Family latrine ownership played a significant mediating role in the relationship between behavioral and environmental factors and diarrheal incidence. These findings highlight the importance of integrated community-based sanitation interventions, supported by behavioral change strategies and strengthened roles of health workers, to effectively reduce diarrheal incidence among under-five children..